ETUDE BIBIOGRAPHIQUE SUR LE TRANSFERT EMBRYONNAIRE CHEZ LES BOVINS - Ghebrini, Med elhadi (My University, 2021)
Embryo transfer or embryo transplantation consists of collecting embryos from a living female, called a “donor”, which will then be transferred to recipient females. The main objectives of embryo transfer are better use of females with high genetic potential, and simplified dissemination of this genetics. In addition, the genetic dissemination allowed by this method is the safest in terms of health, which is an undeniable advantage. Currently, embryo transfer in the bovine species can be carried out both on-station and in breeding. Thanks to the so-called "cervical" transfer technique, practitioners are in fact free from any invasive intervention. In an embryo transfer, donors and recipients must first be synchronized. Then, superovulation treatment is started on the donors, before artificial insemination is performed. The embryos are collected seven days later, then evaluated before being washed. Embryos can be transferred fresh, that is, the same day of collection, when recipients are ready, otherwise they can be frozen and then stored in liquid nitrogen at -196 ° C. The IETS (International Embryo Transfer Society) gives the instructions to be followed in order to guarantee the health security of the transfer. Combined with the ease of transporting frozen embryos, this security allows for large-scale genetic dissemination